2003
DOI: 10.1677/joe.0.1780111
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal changes in type-2 diabetic Goto-Kakizaki rats

Abstract: We characterized appendicular and axial bones in rats with type-2 diabetes in five female Goto-Kakizaki (GK) rats, a strain developed from the Wistar rat showing spontaneous type-2 diabetes, and five age-and sex-matched nondiabetic Wistar rats. The humerus, tibia, metatarsals and vertebral bodies were analysed by peripheral quantitative computerized tomography (pQCT). In diabetic rats, the height of the vertebral bodies and length of the humerus were decreased while the length of the metatarsals was increased.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 42 publications
2
38
1
Order By: Relevance
“…For example, type 2 diabetic patients have an increased fracture risk independently of areal BMD (Schwartz et al 2001, Strotmeyer et al 2005 and their circulating osteocalcin levels are low (Okazaki et al 1997). Consistent with our results, mid-shaft cortical bones of type 2 diabetic rats showed expansion of periosteal and endosteal circumferences (Ahmad et al 2003) and vitamin K treatment improved bone fragility by modifying minerals in these rats (Wada et al 2000).…”
Section: Discussionsupporting
confidence: 88%
“…For example, type 2 diabetic patients have an increased fracture risk independently of areal BMD (Schwartz et al 2001, Strotmeyer et al 2005 and their circulating osteocalcin levels are low (Okazaki et al 1997). Consistent with our results, mid-shaft cortical bones of type 2 diabetic rats showed expansion of periosteal and endosteal circumferences (Ahmad et al 2003) and vitamin K treatment improved bone fragility by modifying minerals in these rats (Wada et al 2000).…”
Section: Discussionsupporting
confidence: 88%
“…The estimated bending strength of the humeral and tibial diaphyses in Goto-Kakizaki rats has been reported to be higher relative to Wistar control animals (Ahmad et al 2003). The present study offers a more complete determination of bone strength changes with type 2 diabetes, with direct measurement of mechanical properties during the three stages of development and progression of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 61%
“…By 20 weeks of age, these long bones were 7-8% shorter than bones of age-matched lean controls. Interestingly, the increase in long bone diameters and CSMI observed in Goto-Kakizaki rats, another rodent model of type 2 diabetes (Ahmad et al 2003), was not observed in the ZDF rats. In fact, data from the present study provide evidence for reduced radial growth as illustrated by smaller CSMI values in the long-term diabetic (20 weeks of old) rats.…”
Section: Discussionmentioning
confidence: 93%
“…Differences in bone structure, BMD and fragility phenotypes between inbred strains of rats have been identified including the non-diabetic F344 and the type-2 diabetic GK strain [8][9][10].…”
Section: Introductionmentioning
confidence: 99%